2005
DOI: 10.1038/sj.bjp.0706059
|View full text |Cite
|
Sign up to set email alerts
|

2‐Furoyl‐LIGRL‐NH2, a potent agonist for proteinase‐activated receptor‐2, as a gastric mucosal cytoprotective agent in mice

Abstract: 1 Proteinase-activated receptor-2 (PAR 2 ), expressed in capsaicin-sensitive sensory neurons, plays a protective role in gastric mucosa. The present study evaluated gastric mucosal cytoprotective effect of 2-furoyl-LIGRL-NH 2 , a novel highly potent PAR 2 agonist, in ddY mice and in wild-type and PAR 2 -knockout mice of C57BL/6 background. 2 Gastric mucosal injury was created by oral administration of HCl/ethanol solution in the mice. The native PAR 2 -activating peptide SLIGRL-NH 2 , administered intraperiton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Ample evidence indicates PAR2 receptors mediate prono- ciceptive and proinflammatory effects through a neurogenic mechanism of action (Ricciardolo et al, 2000;Steinhoff et al, 2000;Fiorucci et al, 2001;Vergnolle et al, 2001;Nguyen et al, 2003;Kawabata et al, 2005;Su et al, 2005). Treatment with PAR2 APs or trypsin can stimulate the release of CGRP and substance P from both central and peripheral terminals of primary afferent nociceptive neurons, which in turn may mediate states of pain and inflammation .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ample evidence indicates PAR2 receptors mediate prono- ciceptive and proinflammatory effects through a neurogenic mechanism of action (Ricciardolo et al, 2000;Steinhoff et al, 2000;Fiorucci et al, 2001;Vergnolle et al, 2001;Nguyen et al, 2003;Kawabata et al, 2005;Su et al, 2005). Treatment with PAR2 APs or trypsin can stimulate the release of CGRP and substance P from both central and peripheral terminals of primary afferent nociceptive neurons, which in turn may mediate states of pain and inflammation .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, single high doses of PAR2 agonists inhibit infiltration of inflammatory cells into the lungs and reduce airway resistance of lipopolysaccharide-challenged mice and ovalbumin sensitized mice (Moffatt et al, 2002;De Campo and Henry, 2005;Morello et al, 2005), whereas administration of multiple doses of SLIGRL-NH 2 or genetic overexpres- at ASPET Journals on May 9, 2018 jpet.aspetjournals.org Downloaded from ulcer PAR2 agonists prevent/limit tissue damage to the stomach lining by inducing mucus secretion, possibly through a neurogenic mechanism (Kawabata et al, 2005). Likewise, cerulein-induced pancreatitis and associated abdominal hyperalgesia/allodynia were exacerbated in PAR2 knockout mice and suppressed by 2-furoyl-LIGRLO-NH 2 in WT, but not PAR2, knockout mice (Kawabata et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAR1 and PAR2 play multiple roles in the gastric mucosa in rats and/or mice, being primarily protective (Kawabata et al, 2001a;Kawabata et al, 2004c). However, the underlying mechanisms for the gastric mucosal protection caused by PAR1 and PAR2 activation are largely different; i. e. the protective effect of PAR1 agonists is dependent on PGs formation (Kawabata et al, 2004c), whereas PAR2 agonists elicit gastric mucus secretion and mucosal protection by activating sensory neuron, an effect being independent of PGs (Kawabata et al, 2001a;Kawabata et al, 2005). COX-1-derived PGs appear to predominantly mediate the PAR1-triggered gastric mucosal protection, since a COX-1 inhibitor, SC-560, but not a COX-2 inhibitor, NS-398, abolished the protective effect (Kawabata et al, 2004c).…”
Section: Prostanoid-dependent Functions Of Par1 In Gastric Mucosamentioning
confidence: 96%
“…Experiments on rat model of ethanol ulcer showed that PAR1-AP injected intravenously with amastatin (aminopeptidase inhibitor) protected the gastric mucosa in mild injuries [4]. Moreover, the protective effect of PAR2 agonist peptide (2-furoyl-LIGRL) was demonstrated on the model of gastric mucosa injury induced by ethanol and HCl [5].…”
mentioning
confidence: 96%